Transformative Scenario Planning: A Tool for Systemic Change - Kahane, Adam (Institutional Knowledge at Singapore Management University, 2013)
A leading organiser, designer and facilitator of processes involving tri-sector collaboration, Adam Kahane shares with Social Space on how transformative scenario planning takes scenario planning to a new level and works as a powerful tool for systemic change.